Sunshine and health : . The nudist : sunshine and health
(1936) titled: The nudist; since (1937): The nudist. Sunshine and health; since (1940): Sunshine and health. The nudist; Since 21(1952):no.11 subtitled: Official journal of the National Nudist Council.